An inconsistent phase selection assessment for harmonic peaks elimination in operational modal testing - Ong, Zhi Chao; Lim, Hong Cheet; Brandt, Anders; Ismail, Zubaidah; Khoo, Shin Yee (Springer, 2019)
An improvement on modal analysis technique is always exacerbated by the limitation on both operational modal analysis (OMA) and experimental modal analysis (EMA). In a recent year, a novel method was introduced named impact-synchronous modal analysis (ISMA) which represents a magnificent achievement in this field. The efficiency of this method as a viable option for EMA and OMA is proven in previous research. However, a quick and straightforward real-time ISMA method is desired as the current procedure is labour-intensive and time-consuming due to the lack of control on the impact timing with respect to phase angle of the disturbances. Thus, the aim of this paper is to identify the significance of phase difference information between acceleration response and cyclic load component in eliminating the disturbances through impact-synchronous time averaging. The paper presented a phase selection assessment, and the results showed that a few averages, (i.e. four averages) are sufficient to filter out the disturbances by 72–80% of dominant periodic response due to cyclic load and over 50% reduction for second harmonic, when the phase angles with respect to the impact are inconsistent for each impact applied. A better modal identification result is obtained through a straightforward way of eliminating the periodic response. Thus, the estimated frequency response function is strongly enhanced and good correlation is observed between modal extraction data and benchmark EMA result. © 2019, Springer-Verlag GmbH Germany, part of Springer Nature.